SAKSI TALAK MENURUT IM?M AL-SY?FI’? - Ahmad Fauzi; Syamsul A'dlom (MAQASHID Jurnal Hukum Islam, 2019)
Scholars differ about the necessity of witnesses in divorce. There are those who oblige, say the Sunnah, and while others say that divorce does not need a witness. These differences stem from an understanding of related sacred texts that are also diverse. In addition, those with their opinions hold their own logic. In Indonesia itself, the witness' obligation is regulated in positive Islamic law or KHI. Divorce must be resolved through the Religious Courts. This means that the existence of witnesses in the divorce process in Indonesia is a necessity, as a form of efforts to protect the rights of all related parties. Imam al-Shafi'i in his magnum opus, al-Umm, said that witnesses in divorce and reconciliation were the same as the position of witnesses in the sale and purchase agreement or other trade transactions that were highly recommended for the benefit of the people.